Access Stories ... and a Bit More: A Talking Circle Inspired Discussion (LEARNing Landscapes, 2016)
This paper focuses on what happened when a doctoral student wanted to study an Indigenous group’s approach to leadership. Three accounts are presented: the student’s, her advisor’s, and an Indigenous culture leader’s. The accounts were developed and are being reported by using a modi ed version of the talking circle process employed in many Indigenous cultures. Despite modi cations, the approach retained many of the characteristics of traditional talking circles and demonstrated a talking circle’s potential for "transforming understanding through creative engagement."
Keywords: leadership; indigenous; transformation; talking circle; creative engagement